Ajulemic acid, a nonpsychoactive cannabinoid acid, induces apoptosis in human T lymphocytes - Bidinger, Bonnie (Clinical immunology (Orlando, Fla.), 2003)
Oral administration of ajulemic acid (AjA), a synthetic nonpsychoactive cannabinoid acid, prevents joint cartilage and bone damage in an experimental model of arthritis in rats. Joint tissue injury in patients with rheumatoid arthritis (RA) is due in part to activation of T lymphocytes in the synovium, and T lymphocytes in synovium of RA patients are resistant to apoptosis. Thus, a potential mechanism whereby AjA prevents joint tissue injury in the animal model might be enhanced apoptosis of T lymphocytes. Apoptosis of human T cells in vitro was assessed by Annexin V expression, caspase-3 activity, DNA fragmentation, and microscopy. AjA induced apoptosis of T cells in a dose- and time-dependent manner. Apoptosis preceded loss of cell viability by trypan blue dye exclusion, confirming that cell loss was due to programmed cell death rather than necrosis. A nontoxic compound such as AjA may be a useful therapeutic agent for patients with diseases such as RA which are characterized by T-cell-driven chronic inflammation and tissue injury